Diffuse cutaneous systemic sclerosis following SARS-Co V-2 vaccination. Issue 128 (April 2022) - Cole, Alice; Thomas, Rhys; Goldman, Nina; Howell, Kevin; Chakravarty, Kuntal; Denton, Christopher P.; Ong, Voon H.
Abstract: The largest world-wide vaccination rollout ever is currently underway to tackle the covid-19 pandemic. We report a case of diffuse cutaneous systemic sclerosis (SSc) in a 70-year-old male with rapidly progressive skin thickening which developed two weeks after receiving the first dose of the ChAdOx1 nCOV-19 vaccine. As the onset of SSc skin was in close temporal proximity to the administration of the first dose vaccine with no other triggers, we suspected a possible adverse reaction to the ChAdOx1 nCOV-19 vaccine. We hypothesise that the recombinant adenoviral vector encoding the spike protein antigen of SARS-CoV-2 triggered an unexpected immune activation resulting in an atypical presentation of late-onset SSc, within the well-recognised ANA positive, ENA negative subgroup of patients.We review the possible mechanisms underlying autoimmunity when provoked by vaccination and other published rheumatological phenomenon occurring shortly after COVID vaccination. Highlights: A case of diffuse systemic sclerosis after vaccination with ChAdOx1 vaccine. Mechanisms of autoimmunity include 'bystander effect' and molecular mimicry. There may be a pathological role for endosomal TLR9-driven activated B cells. Review of rheumatological phenomenon observed following COVID vaccination.